Evaluating Recharge Options for Phase-Change Material Storage of a Personal Conditioning System. (26th November 2019) - Dhumane, Rohit; Qiao, Yiyuan; Muehlbauer, Jan; Ling, Jiazhen; Aute, Vikrant; Hwang, Yunho
Abstract : The Roving Comforter (RoCo) is a vapor compression-cycle-based personal conditioning system (PCS). It stores its condenser waste heat into a phase-change material (PCM)-based thermal storage. When the PCM is completely melted, the PCM storage needs to be recharged before the next cooling operation. This may be conducted in two different ways: (i) a two-phase thermosiphon operation that consumes much less power and requires a longer recharge time (∼6.5 h), or (ii) a heat pump operation that consumes more power with a much shorter operation time (∼2.5 h). The objective of this article is to analyze the merits and demerits of these two recharge operations. A validated dynamic model of the thermosiphon and heat pump in Modelica is used to evaluate the overall coefficient of performance for combined cooling and recharge operations. The modeling framework discussed here is fairly generic and facilitates investigating vapor compression cycle integration strategies with PCM storage modes. The article provides interesting insights and quantification of benefits obtained from various strategies adopted for improving the PCS.